Sensitive determination of water insoluble dyes used as marking of commercial petroleum products using high-performance liquid chromatography with electrochemical detection - Trindade, Magno Aparecido Gonçalves [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP]; Matysik, Frank-Michael (Wiley, 2010)
This paper describes an analytical method using high-performance liquid chromatographic (HPLC) separation coupled with electrochemical detection to detect three dyes, Solvent Blue 14 (SB-14), Solvent Blue 35 (SB-35) and Solvent Red 24 (SR-24). The dyes were eluted and separated using a reversed-phase column (C-8) under isocratic elution with the mobile phase containing a mixture of acetonitrile/ammonium acetate (5.0 mmol L -1) at the ratio of 75:25 (v/v). Two sample pretreatment methods were tested and successfully applied to quantify SB14, SB-35 and SR24 dyes in gasoline samples. The proposed method was simple, fast and suitable to detect and quantify marker dyes in gasoline sample at low concentration. © 2010 Wiley-VCH Verlag GmbH &Co. KGaA, Weinheim.
Keywords: Dyes; Electrochemical detector; Fuel; Liquid chromatography; Marker dyes; Petrol sample; Solvent dyes